A secondary battery

CN122393389BActive Publication Date: 2026-10-23CALB GROUP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610839458.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-11
Publication Date
2026-10-23
Estimated Expiration
2046-06-11

AI Technical Summary

Technical Problem

[0002]二次电池中负极极片主要包括石墨系负极极片、硅系负极极片等,均属于现阶段较为成熟且安全的极片种类,但是现有的负极极片因负极材料传质速率限制,导致电池的快充性能始终无法有效提升至较高水平,虽然也有部分经过活性材料结构化设计的负极极片可以在一定程度上改善快充性能,但是又会因负极极片与电解液的副反应过多而造成循环性能下降的情况

Benefits of technology

本申请提供了一种二次电池,通过对负极极片中负极材料特定范围的孔隙体积占比、负极极片的面电阻以及负极极片的电解液浸润系数进行协同调控,不仅可以有效提升二次电池的快充性能,同时负极极片与电解液的副反应少,活性锂损失少,循环稳定性高,二次电池的循环寿命长。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The application discloses a secondary battery and belongs to the technical field of batteries. The secondary battery is synergistically controlled in terms of the specific range of the pore volume proportion of the negative electrode material in the negative electrode sheet, the surface resistance of the negative electrode sheet and the electrolyte infiltration coefficient of the negative electrode sheet. The secondary battery can effectively improve the fast-charging performance, the side reaction between the negative electrode sheet and the electrolyte is small, the loss of active lithium is small, the cycle stability is high, and the cycle life of the secondary battery is long.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery technology, specifically to a secondary battery. Background Technology

[0002] The negative electrode sheets in secondary batteries mainly include graphite-based negative electrode sheets and silicon-based negative electrode sheets, which are all relatively mature and safe electrode sheet types at present. However, due to the limitation of the mass transfer rate of the negative electrode material, the fast charging performance of the battery has not been able to be effectively improved to a high level. Although some negative electrode sheets with structured active material design can improve the fast charging performance to a certain extent, the cycle performance will decline due to excessive side reactions between the negative electrode sheet and the electrolyte. Summary of the Invention

[0003] The purpose of this application is to overcome the shortcomings of the existing technology and provide a secondary battery. By synergistically controlling the pore volume ratio of the negative electrode material in a specific range, the surface resistance of the negative electrode, and the electrolyte wetting coefficient of the negative electrode, the fast charging performance of the secondary battery can be effectively improved. At the same time, there are fewer side reactions between the negative electrode and the electrolyte, less loss of active lithium, high cycle stability, and long cycle life of the secondary battery.

[0004] To achieve the above objectives, in a first aspect of this application, a secondary battery is provided, comprising a negative electrode sheet and an electrolyte, wherein the negative electrode sheet comprises a negative electrode active material layer, and the negative electrode active material layer comprises a negative electrode material. The secondary battery satisfies: (a×c) / b=0.12~53.6; The percentage a% is the volume percentage of pores with a diameter ≥ 30 nm in the total pore volume of the negative electrode material. The b mΩ is the surface resistance of the negative electrode plate; The c mm.s -1 / 2 is the electrolyte wetting coefficient of the negative electrode.

[0005] The beneficial effects of this application are as follows: This application provides a secondary battery that, by synergistically controlling the pore volume ratio of the negative electrode material within a specific range, the sheet resistance of the negative electrode, and the electrolyte wetting coefficient of the negative electrode, can not only effectively improve the fast-charging performance of the secondary battery, but also reduce the side reactions between the negative electrode and the electrolyte, minimize the loss of active lithium, achieve high cycle stability, and extend the cycle life of the secondary battery. Detailed Implementation

[0006] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0007] In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features.

[0008] In this application, numerical ranges are referred to as continuous unless otherwise specified, and include the minimum and maximum values ​​of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values ​​of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are incorporated.

[0009] The present application is further illustrated below with specific embodiments: A secondary battery includes a negative electrode sheet and an electrolyte, wherein the negative electrode sheet includes a negative electrode active material layer, and the negative electrode active material layer includes a negative electrode material; The secondary battery satisfies: (a×c) / b=0.12~53.6; The percentage a% is the volume percentage of pores with a diameter ≥ 30 nm in the total pore volume of the negative electrode material. The b mΩ is the surface resistance of the negative electrode plate; The c mm.s -1 / 2 is the electrolyte wetting coefficient of the negative electrode.

[0010] To improve the fast-charging performance of secondary batteries while maintaining a long cycle life, the solution described in this application involves synergistic regulation of the pore size distribution of the negative electrode material, particularly the volume ratio (a) of pores with a diameter ≥30 nm, and the electrolyte wetting coefficient (c) of the negative electrode. Compared to micropores and small mesopores, mesopores and macropores with a diameter greater than 30 nm in the negative electrode material exhibit higher electrolyte wettability and facilitate rapid unidirectional diffusion of the electrolyte from the surface of the negative electrode material into the interior. Adjusting the proportion of this pore size in conjunction with the electrolyte wetting coefficient of the electrode improves the wetting effect of the negative electrode when in contact with the electrolyte, enhances its liquid retention capacity, reduces polarization, and provides abundant transport channels and sites for lithium ions to intercalate and deintercalate on the electrode. The improved insertion / extraction efficiency, along with the control of the sheet resistance (b) of the negative electrode, significantly increases the deposition rate of lithium ions on the negative electrode and reduces the transport resistance within the electrode, ultimately enhancing the fast-charging performance of the secondary battery. However, if the volume ratio of pores larger than 30nm is too large, or if the electrolyte wetting coefficient of the negative electrode is too high, the electrolyte's wetting rate on the negative electrode will be too fast, resulting in an excessively large actual wetting area. This increases the side reactions between the negative electrode and the electrolyte, leading to the loss of active lithium and affecting the cycle stability of the secondary battery. On the other hand, if the sheet resistance of the negative electrode is too low, the deposition rate of lithium ions on the negative electrode surface will be too fast, increasing the probability of lithium dendrite formation, damaging the SEI film, and requiring additional active lithium for repair, which will also weaken the cycle performance of the secondary battery. When the three factors mentioned above in the secondary battery are synergistically regulated, if the ratio of the relationship between the three factors (a×c) / b is controlled within the range of 0.06 to 58, the rapid lithium-ion insertion / extraction transport capability and the cycle stability of the negative electrode in the secondary battery can be effectively balanced, so that the secondary battery ultimately exhibits excellent fast charging performance and cycle performance.

[0011] In some implementations, (a×c) / b = a range of one or both of the following: 0.12, 0.3, 0.5, 1, 1.9, 2, 5, 5.5, 6, 7, 10, 15, 20, 30, 50, 52, 53, 53.6.

[0012] More preferably, the secondary battery satisfies: (a×c) / b=0.5~5.5.

[0013] As mentioned above, when the pore size distribution of the negative electrode material in a secondary battery, especially the volume ratio (a) of pores with a pore size ≥30nm, the sheet resistance (b) of the negative electrode sheet, and the electrolyte wetting coefficient (c) of the negative electrode sheet are synergistically controlled, it is possible to avoid the blockage of electrolyte wetting channels due to the porosity of the negative electrode material, resulting in poor electrolyte wetting of the negative electrode sheet and hindered lithium-ion transport. At the same time, the transport resistance inside the electrode sheet is relatively small, giving the secondary battery high fast-charging performance, and also ensuring the stability of the negative electrode sheet during cycling. The electrolyte does not excessively wet the negative electrode, resulting in fewer side reactions. At the same time, the deposition rate of lithium ions on the negative electrode surface is moderate, the probability of lithium dendrite formation is low, the SEI film has good stability, and the amount of irreversible loss of active lithium is small. When the relationship between these three factors is further adjusted and optimized to the above-mentioned preferred range, the lithium ion transport kinetics in the battery are better, there are fewer side reactions between the negative electrode and the electrolyte, the SEI film on the surface of the negative electrode is more stable, and the secondary battery can have better fast charging performance and cycle performance.

[0014] In some implementations, a% = 20%~60%.

[0015] In some implementations, a% is a range of one or any two of 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, and 60%.

[0016] More preferably, a% = 35%~55%.

[0017] When the volume ratio of pores larger than 30nm in the negative electrode material is relatively large, it can provide sufficient wetting channels for the electrolyte, which can improve the transport efficiency of lithium ions inside the battery, especially between the electrode and the electrolyte. However, if the proportion is too large, it will lead to an excessively large actual contact area between the electrolyte and the negative electrode material, resulting in more side reactions and thus more irreversible loss of active lithium. After the secondary battery is synergistically regulated by a, b, and c, further optimizing the volume ratio of pores larger than 30nm in the negative electrode material to a% within the above range can further improve the balance between lithium ion transport performance and interface stability of the negative electrode, and further improve the cycle and fast charging performance of the secondary battery.

[0018] It should be noted that the a% mentioned in this application can be confirmed in, but is not limited to, the following ways: The secondary battery was discharged at a rate of 0.33C to the lower voltage limit of 2.5V. The negative electrode was then disassembled and immersed in dimethyl carbonate (DMC) solution for 4 hours. After drying, the active material layer of the negative electrode was scraped off to obtain negative electrode material powder. 100mg of this powder was weighed and placed in a sample tube. The sample tube was then installed in the degassing station of a fully automated specific surface area and pore size analyzer. Degassing was performed under vacuum at 80°C for 6 hours to thoroughly remove adsorbed moisture, gases, and other volatile impurities from the sample surface. After degassing, the sample tube was transferred to the analysis station. Under the cryogenic environment of liquid nitrogen, the system automatically introduced nitrogen gas at different partial pressures into the sample tube and accurately measured the sample at different relative pressures (P / P0). The amount of nitrogen adsorbed at a point is measured until the relative pressure approaches 1, obtaining a complete nitrogen adsorption-desorption isotherm. Using the BET (Brunauer-Emmett-Teller) model, the specific surface area of ​​the sample is calculated within a linear range of 0.05-0.30 relative pressure (P / P0). Using the BJH (Barrett-Joyner-Halenda) model or other suitable DFT / NLDFT models, the pore size distribution and average pore size of the sample are calculated from the desorption or adsorption isotherms. At least two parallel samples are tested for each batch to ensure good parallelism of the results. The system outputs the average data of specific surface area, pore volume, and pore size distribution. The volume ratio 'a' of pores with a pore size ≥30nm in the total pore volume is obtained by integrating the adsorption-desorption curves.

[0019] In some implementations, b = 0.5~20mΩ.

[0020] In some implementations, b is a range of one or both of the following: 0.5 mΩ, 1 mΩ, 2 mΩ, 2.5 mΩ, 5 mΩ, 6 mΩ, 8 mΩ, 10 mΩ, 12 mΩ, 15 mΩ, 18 mΩ, and 20 mΩ.

[0021] More preferably, b = 2.5~10mΩ.

[0022] The sheet resistance of the negative electrode directly affects the cycle performance and fast-charging performance of the secondary battery. When the sheet resistance b of the negative electrode is low, the internal transport resistance of the negative electrode is small, and the rate of lithium ion deposition is high. Although this can improve the transport efficiency, it also increases the probability of lithium dendrite formation, which can easily damage the SEI film on the electrode surface. This leads to repeated repair-breakage cycles and continuous consumption of active lithium. On the other hand, if the sheet resistance b is large, it means that the lithium ion transport resistance inside the electrode is high. When the secondary battery is specifically controlled based on (a×c) / b, and the sheet resistance b of the negative electrode is further optimized to be within the above range, it can not only ensure the high efficiency of lithium ion transport on the electrode, but also reduce the probability of lithium dendrite formation, ultimately achieving a better balance between cycle performance and fast-charging performance.

[0023] It should be noted that the surface resistance b of the negative electrode sheet described in this application can be confirmed by, but is not limited to, the following methods: The secondary battery was discharged at a rate of 0.33C to the lower voltage limit of 2.5V. The negative electrode was then disassembled and soaked in dimethyl carbonate (DMC) solution for 4 hours, then dried. The negative electrode was cut into 14mm diameter round pieces, ensuring a smooth surface free of creases, burrs, and material loss. The sample was placed in the center of the sample stage of the Chuanyuan membrane resistance tester. The black knob on the lower right of the mold was manually rotated counterclockwise, lowering the upper probe to the sample surface. The resistance and pressure were read when the pressure reached 0.4MPa. The knob was then rotated clockwise, raising the upper probe, and the sample was replaced. The above steps were repeated to test three parallel samples. After reaching the set number of parallel samples, the average value was automatically output, which is the sheet resistance b of the negative electrode.

[0024] In some embodiments, c = 0.1~0.5 mm·s -1 / 2 .

[0025] In some implementations, c = 0.1 mm·s -1 / 2 0.12 mm.s -1 / 2 0.15 mm.s -1 / 2 0.18mm.s -1 / 2 0.2 mm.s -1 / 2 0.25 mm.s -1 / 2 0.3 mm.s -1 / 2 0.35 mm.s -1 / 2 0.4 mm.s -1 / 2 0.45mm.s -1 / 2 0.5 mm.s -1 / 2 The range of one or any two of them.

[0026] More preferably, c = 0.12~0.3 mm·s -1 / 2 .

[0027] When the electrolyte wetting coefficient of the negative electrode is low, the electrolyte's wetting effect on the negative electrode is poor, resulting in high resistance to lithium-ion transport on the negative electrode and a high polarization effect. Conversely, if the wetting coefficient is too high, it will lead to excessive contact between the electrolyte and the negative electrode material on the negative electrode, increasing side reactions and the consumption of active lithium. Therefore, it is necessary to coordinate the control of the large pore volume ratio of the negative electrode material and the sheet resistance of the negative electrode to ensure the fast-charging performance and cycle performance of the secondary battery. When the electrolyte wetting coefficient of the negative electrode is further optimized within the above-mentioned range after the three factors are controlled, the wetting effect of the electrolyte on the negative electrode in the secondary battery can be further improved, the resistance to lithium-ion transport can be reduced, and the relative stability between the electrode and the electrolyte can be maintained, ultimately effectively improving the overall performance of the secondary battery.

[0028] It should be noted that the electrolyte wetting coefficient c of the negative electrode sheet described in this application can be confirmed by, but is not limited to, the following methods: The secondary battery was discharged at a rate of 0.33C to the lower voltage limit of 2.5V. The negative electrode was then disassembled and immersed in dimethyl carbonate (DMC) solution for 4 hours, followed by air drying. At 25°C and in an Ar gas atmosphere, a container filled with electrolyte was placed on a liftable platform, the displacement of which was precisely controlled by a motor. The resulting negative electrode sample was suspended on an electronic balance connected to a data acquisition device. The motor was adjusted to raise the height of the liftable platform, ensuring the electrode sample was submerged 5mm above the electrolyte level in the container. The data acquisition device recorded the weight of the electrode sample in real time. The wetting rate of the electrolyte on the negative electrode was calculated using the Lucas-Washburn equation, the specific formula of which is as follows: ; Where t is the time the negative electrode is immersed in the electrolyte, in seconds; Δm is the mass change of the electrode after absorbing the electrolyte, in grams; and ρ is the electrolyte density, in g / cm³. 3 A is the cross-sectional area of ​​the electrode; K is the wetting rate of the electrolyte on the negative electrode. Plot a mass-time curve, where the horizontal axis is the square root of time and the vertical axis is mass / (sample cross-sectional area × electrolyte density). Perform linear fitting on the curve during the electrolyte wetting stage. The slope of the fitted line is the wetting rate K. Then K is the electrolyte wetting coefficient c of the negative electrode. The electrolyte is prepared by mixing ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) in a volume ratio of 1:1:1 to obtain an organic solvent, adding 4% by mass of vinylene carbonate as an additive, and using LiPF6 as a lithium salt at a concentration of 1 mol / L to obtain the electrolyte.

[0029] In some embodiments, the secondary battery satisfies: x% = 5%~30%, where x% is the volume percentage of pores with a diameter ≤10nm in the negative electrode material in the total pore volume.

[0030] In addition to larger pores of 30nm and above, the optimized control of small pores (including micropores and some mesopores) of 10nm and below can also effectively improve the fast charging performance of secondary batteries. When the volume ratio of the small pores is controlled within the above range, it can not only provide more sites and channels for lithium ion insertion and extraction, but also control the liquid retention capacity of the negative electrode, reduce the polarization effect, and improve the rapid transport capability of lithium ions.

[0031] In some embodiments, the secondary battery satisfies: y% = 5%~45%, where y% is the volume percentage of pores with a diameter ≥ 50nm in the negative electrode material in the total pore volume.

[0032] In the negative electrode sheet, the larger pore size of the negative electrode material mainly affects the wetting and liquid retention effect of the electrolyte on the negative electrode material. After controlling the volume ratio of pores larger than 30nm, further controlling the volume ratio of pores larger than 50nm can effectively balance the wetting effect of the negative electrode sheet and improve fast charging performance. At the same time, it can also avoid the increase of side reactions caused by excessive contact between the electrolyte and the negative electrode material, which would affect the cycle performance of the secondary battery.

[0033] It should be noted that the test methods for x% and y% described in this application are the same as those for a%.

[0034] In some embodiments, the negative electrode material includes a mesoporous material.

[0035] It should be noted that the mesoporous material refers to a material containing mesopores, that is, pores with a diameter in the range of 2 to 50 nm.

[0036] Furthermore, the mesoporous material includes at least one of mesoporous oxides, mesoporous nitrides, mesoporous carbides, mesoporous elements, and mesoporous metal-organic framework materials.

[0037] In some embodiments, the mesoporous oxide includes at least one of mesoporous non-metallic oxides and mesoporous metallic oxides. The mesoporous non-metallic oxide can be mesoporous silicon dioxide, and the mesoporous metallic oxide can be mesoporous titanium dioxide, mesoporous tin dioxide, mesoporous iron oxide, mesoporous cobalt oxide, mesoporous magnesium oxide, etc. The mesoporous nitride can be mesoporous carbon nitride, and the mesoporous carbide can be a mesoporous metallic carbide, such as mesoporous iron carbide. The mesoporous element can be mesoporous carbon, and the mesoporous organometallic framework material (mesoporous MOFs) can be mesoporous ZIF-8, mesoporous ZIF-7, mesoporous aluminum-based MIL-100, mesoporous iron-based MIL-100, mesoporous MOF-5, etc.

[0038] By introducing mesoporous materials into the negative electrode material, the volume ratio of pores of 30nm and above in the negative electrode material can be adjusted. This material has a high specific surface area and mesoporous characteristics, which can effectively improve the liquid retention capacity of the negative electrode sheet, thereby improving the fast charging performance of the secondary battery. Those skilled in the art can choose whether to add it and the type of material to add according to actual needs, without making specific limitations.

[0039] In some embodiments, the negative electrode material includes a mesoporous oxide, which is an oxide of element X, and the mass percentage of element X in the negative electrode active material layer is 0.06~2%, and element X includes at least one of Si, Al, W, Zn, Cu, V, and Ti.

[0040] As mentioned above, introducing mesoporous oxide into the negative electrode material can effectively improve the electrolyte retention capacity of the negative electrode sheet, reduce the obstruction of the wetting channels, and lower the resistance to lithium-ion transport. Specifically, the content of element X in the oxide can, to a certain extent, represent the content of mesoporous oxide. When the proportion of mesoporous oxide is further controlled within the above range, the lithium-ion transport efficiency in the secondary battery can be optimized while avoiding excessive filling of the gaps between negative electrode material particles by mesoporous oxide, which would increase the electrode resistance and affect the cycle performance of the secondary battery.

[0041] It should be noted that the mass content of element X in the negative electrode active material layer can be confirmed by, but is not limited to, the following methods: The secondary battery was discharged at a rate of 0.33C to the lower voltage limit of 2.5V. The battery was disassembled to obtain the negative electrode sheet. The negative electrode sheet was immersed in DMC at 25℃ for 60 minutes, dried, and the negative electrode active material layer was scraped off to obtain negative electrode material powder. A certain amount of negative electrode material powder was weighed and dispersed in 20mL of water. Then, 10mL of nitric acid was added, and the mixture was heated until the negative electrode material powder dissolved. The material was diluted with water to 100mL to obtain the test solution. The test solution was subjected to ICP testing. Before the test, a standard solution must be prepared. The linear correlation coefficient of the standard concentration must be above 0.999 to be used as a normal standard. The 1000 mg / L standard solution was diluted with deionized water to different concentrations (generally 0, 1 mg / 100mL, 2 mg / 100mL, and 3 mg / 100mL). The element detection wavelength was selected, and the experimental conditions were set: based on the sample characteristics and the element to be detected, appropriate ICP instrument operating conditions were set: gas flow rate 0.5 L / min, power 1150 W. The element detection wavelength was selected, and the content of element X in the sample could be read using the self-analysis function of the ICP testing software. The standard solution refers to a solution containing the element to be measured, and standard solutions are commercially available.

[0042] More preferably, the secondary battery satisfies: b / d = 250~5000, where d is the mass percentage of element X in the negative electrode active material layer.

[0043] More preferably, the b / d can be a range of one or any two of the following: 250, 500, 800, 1000, 1200, 1500, 2000, 2500, 3000, 3500, 4000, 4500, and 5000.

[0044] As mentioned above, the sheet resistance of the negative electrode directly affects the lithium-ion transport resistance inside the electrode and the lithium-ion deposition rate on the negative electrode surface. When a, b, and c are synergistically regulated and controlled within a limited range, further synergistic matching of the sheet resistance of the negative electrode and the content of the oxide in the mesoporous pores of the electrode can not only effectively improve the liquid retention capacity of the negative electrode, reduce the lithium-ion transport resistance inside the electrode, and reduce the polarization effect, but also prevent the formation of lithium dendrites due to excessively fast lithium-ion deposition rate, or the increase of side reactions between the negative electrode material and the electrolyte due to excessive electrolyte wetting, ultimately achieving better battery fast charging performance and cycle stability.

[0045] In some embodiments, the tortuosity of the negative electrode sheet is 3 to 15.

[0046] In some embodiments, the tortuosity of the negative electrode sheet is a range of one or both of the following: 3, 4, 5, 6, 8, 10, 12, and 15.

[0047] After adjusting the electrolyte wetting coefficient and surface resistivity of the negative electrode sheet, the tortuosity of the negative electrode sheet is further optimized. When it is within the above range, the migration path of lithium ions on the negative electrode sheet can be effectively shortened, the transmission resistance can be reduced, and the fast charging performance can be improved. At the same time, it can also ensure that the electrode sheet has a sufficient tortuous path to buffer the stress generated during the discharge process, and avoid the breakage or structural damage of the negative electrode material particles during the discharge process, thereby taking into account the high cycle stability of the secondary battery.

[0048] It should be noted that the tortuosity of the negative electrode sheet described in this application can be confirmed by, but is not limited to, the following methods: The secondary battery was discharged at a rate of 0.33C to the lower voltage limit of 2.5V. The negative electrode was obtained by disassembling the secondary battery and then soaked in DMC solution at 25°C for 4 hours and then dried. The negative electrode region was sectioned using a dual-beam electron microscope (FIB, model: SCIOS 2 HiVacFIB). The cutting voltage was 30kV, the cutting beam current was 7nA, and the cutting range was 60μm×65μm×30μm. The imaging voltage was 5kV, and the imaging beam current was 0.8nA. The number of sections was determined based on the z-axis cutting range and the interlayer spacing. For example, when the sample thickness was 30μm and the interlayer spacing was 60nm, the number of sections was approximately 500. The sections were reconstructed in three dimensions, and the pores on the sections were extracted. The centroid of the connecting pores in each section was calculated using software. The tortuosity of adjacent surfaces was calculated by the ratio of the distance between centroids to the straight-line distance between sections. Finally, the tortuosity of the entire negative electrode was calculated. The tortuosity of the negative electrode is T=∑D(i) / H, where D=Cn-Cn-1, d represents the path of the pores between two adjacent surfaces, and H represents the cross-sectional distance of the entire section.

[0049] In some embodiments, the negative electrode material further includes at least one of graphite and silicon-based materials.

[0050] In some embodiments, the graphite includes at least one of natural graphite and artificial graphite, and the silicon-based material includes at least one of elemental silicon, silicon oxide, and silicon-carbon composite materials.

[0051] In some embodiments, the particle size D of the negative electrode material v50 The value is 3~20μm.

[0052] In some embodiments, the particle size D of the negative electrode material v50 The range is one or any two of the following values: 3μm, 4μm, 5μm, 6μm, 8μm, 10μm, 12μm, 15μm, 18μm, and 20μm.

[0053] More preferably, the particle size D of the negative electrode materialv50 The value is 5~15μm.

[0054] It should be noted that the particle size D of the negative electrode material described in this application v50 The test was conducted in the following manner: The secondary battery was discharged at 0.33C to the lower limit voltage of 2.5V for venting treatment. The negative electrode was then disassembled and immersed in dimethyl carbonate solution at 25°C for 4 hours. After drying, the negative electrode active material layer powder was scraped off. The powder was then directly tested using a laser particle size analyzer (Malvin 3000) according to GB / T19077-2016. The particle size D corresponding to a cumulative volume distribution of 50% of the negative electrode material is defined as the particle size of the negative electrode material. v50 .

[0055] By controlling the size of the negative electrode material in the negative electrode sheet, the lithium ion transport path and the stability of the electrode structure can be further optimized. While effectively improving the ion transport efficiency, there will be no excessive contact between the particles and the electrolyte, which could lead to side reactions or particle detachment.

[0056] In some embodiments, the areal density of the negative electrode sheet is 150~270 g / m³. 2 The compacted density is 1.5~1.8 g / cm³. 3 .

[0057] It should be noted that the compaction density and areal density of the negative electrode sheet in this application can be confirmed by, but not limited to, the following test methods. The specific steps are as follows: disassemble the secondary battery, soak the obtained negative electrode sheet in DMC for 4 hours, dry it, and then use a punching machine to punch the negative electrode sheet into a circular sheet of a fixed area, denoted as S0, in mm. 2 Take three circular discs as parallel samples, and weigh each disc using an electronic balance. Record the mass of each disc as M1 (g). Add a suitable amount of deionized water to each disc, gently wipe away the coating with clean paper to expose the current collector, and let stand (dry) at room temperature for 10 minutes. After the current collector is dry, weigh each disc and record the mass as M0. Calculate the surface density using the formula: surface density = (M1 - M0) / S0. Calculate the compacted density of the negative electrode sheet using the formula: (M1 - M0) / (H * S0).

[0058] In some embodiments, the negative electrode sheet further includes a current collector, and the positive electrode active material layer is disposed on at least one side of the current collector.

[0059] In some embodiments, the current collector includes a metal foil, specifically a metal element, such as copper, or a metal alloy, such as at least one of copper alloys and copper-lithium alloys.

[0060] In some embodiments, the tensile strength of the current collector is 200~800MPa.

[0061] When the tensile strength of the current collector of the negative electrode sheet is preferably within the above range, the mechanical relationship between the current collector and the negative electrode material layer disposed on the current collector can be effectively balanced. After the negative electrode sheet is regulated by the porosity of the negative electrode material, the surface resistance of the electrode sheet and the electrolyte wetting coefficient and the lithium ion insertion / extraction rate of the negative electrode sheet is improved, the structural stability of the negative electrode sheet during the cycle is further guaranteed, thereby achieving better fast charging performance and cycle stability.

[0062] In some embodiments, the tensile strength of the current collector in the negative electrode sheet can be confirmed by, but is not limited to, the following methods: The secondary battery is disassembled in a glove box, and a 500mm long current collector sample is cut from the obtained negative electrode sheet using a ceramic knife. After cleaning and drying the sample, five strips are cut longitudinally. The sampling position of the strips must cover the entire width of the foil. When sampling from the edge, the sampling position must be within 5mm of the edge. A universal testing machine is used for testing: the cylinder clamp is replaced, the sensor is confirmed, and the machine is connected to the network. The "Copper Foil Tensile Test Method" is selected. Set the gauge length to 100mm, width to 15mm, and tensile rate to 50mm / min (copper foil); set the thickness parameter to the nominal thickness T corresponding to the foil in the test batch; set the test force zero point, clamp the sample on the testing machine, and ensure that the clamped sample is perpendicular to the clamp under axial tensile force. Click "Start Automatic Test". The sample breaks, the test ends automatically, and the software displays the test results. After the test, it is necessary to confirm whether the sample breaks in the middle. If the break is near the two ends of the clamp, the test result is invalid and a new sample needs to be taken for testing.

[0063] In some embodiments, the negative electrode active material layer may also contain a conductive agent and / or a binder.

[0064] The conductive agent in the negative electrode active material layer is used to provide conductivity. Any conductive agent can be used without particular limitation, as long as it has suitable electronic conductivity and does not significantly cause adverse chemical changes in the battery. For example, the conductive agent includes, but is not limited to, at least one of carbon nanotubes, carbon black, graphite, carbon fibers, activated carbon, mesoporous carbon, and fullerenes, wherein carbon fibers are, for example, carbon nanofibers; and carbon black is, for example, SP, acetylene black, Ketjen black, etc.

[0065] Furthermore, the conductive agent can also be a composite type, such as a mixture of carbon black and carbon nanotubes, and the mass content of the carbon nanotubes in the conductive agent can be 20-80%.

[0066] In some embodiments, the mass percentage of the conductive agent in the negative electrode active material layer is 0.1% to 3%, such as 0.1%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 3%, or any range formed by any two of the above values.

[0067] The binder in the negative electrode active material layer is used to improve the adhesion between negative electrode material particles and the adhesion between the negative electrode material and the negative electrode current collector. Any binder can be used without particular limitation, as long as it has suitable adhesion and does not significantly cause adverse chemical changes in the battery. For example, the binder includes, but is not limited to, at least one of carboxymethyl cellulose (CMC), styrene-butadiene rubber, polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl butyral, and aqueous acrylic resin.

[0068] In some embodiments, the mass percentage of the binder in the negative electrode active material layer is 0.6% to 4.5%, such as 0.6%, 1.0%, 1.2%, 1.5%, 1.8%, 2.0%, 2.2%, 2.5%, 2.7%, 3.0%, 3.2%, 3.5%, 3.8%, 4.0%, 4.2%, 4.5%, or any range formed by any two of the above values.

[0069] In some embodiments, the mass percentage of the negative electrode material in the negative electrode active material layer is 93.5-99%.

[0070] In some embodiments, the negative electrode material can be a commercially available product or a self-made product. When self-made, it can be implemented in the following way: After being crushed, the petroleum coke is calcined at 600-1000℃ for 1-5 hours under a nitrogen atmosphere at a heating rate of 1-10℃ / min, and then graphitized at 2400-2600℃ for 6-12 hours to obtain the negative electrode material.

[0071] It should be noted that the volume ratio of pores with a diameter ≥30nm in the total pore volume of the negative electrode material described in this application can be controlled by the heating rate and calcination temperature, as well as the temperature and time of graphitization treatment during the preparation process of the negative electrode material. Within a certain range, as the heating rate increases, and / or the calcination temperature increases, and / or the temperature and time of graphitization treatment increases, the volume ratio of pores with a diameter ≥30nm in the total pore volume of the negative electrode material generally shows an upward trend. Furthermore, it can also be controlled by introducing mesoporous materials. Within a certain range, as mesoporous materials are introduced and their content increases, the volume ratio of pores with a diameter ≥30nm in the total pore volume of the negative electrode material generally shows an upward trend, but this is not limited to this. Those skilled in the art can also use other methods to control 'a'. In some embodiments, the negative electrode sheet can be prepared in the following manner: The negative electrode material, conductive agent, and binder are compounded and stirred in water to form a slurry, which is then coated onto the current collector. After drying, the slurry forms a layer of negative electrode active material. After further rolling, the negative electrode sheet is obtained.

[0072] In some embodiments, the pressure of the roller pressing is 5~15MPa.

[0073] Furthermore, a mesoporous material, such as a mesoporous oxide, is added to the slurry, wherein the particle size D of the mesoporous material is... v50 The pore size is 5~15μm, and the pores with a pore size of 5~50nm account for 60~85% of the total pore volume in the mesoporous material.

[0074] Furthermore, the slurry comprises a negative electrode material, a conductive agent, a binder, and a mesoporous material, wherein the mass content of the mesoporous material in the material is 0.1-3%.

[0075] It should be noted that the amount of mesoporous material added to the slurry during preparation can be controlled by adjusting the amount of mesoporous material added. As is known to those skilled in the art, the element X corresponding to d is generally Si, Al, W, Zn, Cu, V, Ti, etc. These elements mainly come from mesoporous materials. Within a certain range, d increases with the increase of the amount of mesoporous material added.

[0076] It should be noted that the 'b' mentioned in this application can be controlled by the amount of conductive agent added or the type of conductive agent selected during the preparation of the negative electrode sheet. Within a certain range, as the amount of conductive agent added increases, the sheet resistance 'b' of the negative electrode sheet tends to decrease. At the same time, the introduction of a certain amount of highly conductive agent, such as carbon nanotubes, will also reduce the sheet resistance 'b' of the negative electrode sheet. However, this is not the only method that can be used by those skilled in the art to control 'b'.

[0077] It should be noted that the wetting coefficient c of the negative electrode sheet can be controlled by adjusting the compaction density of the negative electrode sheet. Within a certain range, the higher the compaction density of the negative electrode sheet, the lower the wetting coefficient c of the electrolyte. Specifically, the compaction density can be controlled by the pressure during electrode rolling. Increasing the rolling pressure increases the compaction density, but it is not limited to this. Those skilled in the art can also use other methods to control c.

[0078] In some embodiments, the secondary battery further includes an electrolyte.

[0079] In some embodiments, the viscosity of the electrolyte at 25°C is 1~10 mPa·s.

[0080] More preferably, the viscosity of the electrolyte at 25°C is 2~8 mPa·s.

[0081] It should be noted that the viscosity of the electrolyte described in this application can be confirmed in the following way: The secondary battery was discharged at 0.33C to the lower limit voltage of 2.5V for venting. The battery was then disassembled and the electrolyte collected in a glove box (H2O ≤ 0.1ppm, O2 ≤ 0.1ppm). There are three methods for collecting the electrolyte: After removing the battery cover, ① if there is free electrolyte, collect it into a 5mL sample tube using a pipette and seal it with sealing tape to prevent leakage. ② if there is no free electrolyte, a hydraulic press (Beijing Heng'ao Technology Co., Ltd.'s FY-30 hydraulic press) can be used to continuously pressurize until free electrolyte appears. Collect the electrolyte into a sample tube and seal it. ③ If the first two methods fail to collect the electrolyte, add an appropriate amount of dichloromethane extractant to the battery and record the dichloromethane content. After adding dichloromethane, place the battery in an aluminum-plastic bag and seal it with a heat sealer. Transfer it to an ultrasonic oscillator and oscillate for 12 hours to allow the electrolyte and dichloromethane in the electrode to mix thoroughly. Then, use a pipette to draw the mixture of dichloromethane and electrolyte into a 5mL sample tube and seal the sample tube with sealing tape. After collecting the electrolyte, take it out and test it using a Cambridge viscometer. The Cambridge viscometer is designed based on electromagnetic oscillation viscosity detection technology and uses a magnetically levitated probe for viscosity measurement. Specifically, place the electrolyte in a beaker and control the sample temperature at 25℃ for testing. Read the value after the displayed value stabilizes.

[0082] After optimizing and controlling the negative electrode, the viscosity of the electrolyte in the secondary battery is controlled in this application. This can improve the fluidity of the electrolyte, reduce the resistance to lithium ion transport, and improve the fast charging performance of the secondary battery. It can also prevent the electrolyte from over-wetting the negative electrode, reduce the side reactions between the negative electrode and the electrolyte, reduce the loss of active lithium, and maintain the cycle stability of the secondary battery at a high level.

[0083] In some embodiments, the electrolyte comprises a solvent and a lithium salt.

[0084] In some embodiments, the solvent includes at least one of carbonate solvents, carboxylic acid ester solvents, ether solvents, sulfone solvents, nitrile solvents, and phosphate ester solvents.

[0085] Exemplary examples include, but are not limited to, at least one of propylene carbonate (PC), ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC); carboxylic acid ester solvents include, but are not limited to, at least one of ethyl acetate (EA), methyl formate, and 1,4-butyrolactone; ether solvents include, at least one of dimethyltetrahydrofuran, tetrahydrofuran, and 1,2-dimethoxyethane; sulfone solvents include, at least one of methyl sulfone and dimethyl sulfoxide; nitrile solvents include, at least one of propionitrile, butyronitrile, 1-(2-cyanoethyl)pyrrole, and 1,3,6-hexanetrionitrile; and phosphate ester solvents include, at least one of trimethyl triphosphate and triethyl phosphate.

[0086] In some embodiments, the lithium salt includes at least one of lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium perchlorate, lithium tetrafluoroborate, lithium dioxalate borate, lithium difluorooxalate borate, lithium trifluoromethanesulfonate, lithium difluorosulfonylimide, lithium difluoromethanesulfonylimide, lithium difluoromethanesulfonylimide, lithium difluorodioxalate phosphate, lithium tetrafluorooxalate phosphate, and lithium hexafluoroarsenate.

[0087] In some embodiments, the concentration of the lithium salt in the electrolyte is 0.5~2 mol / L.

[0088] In some embodiments, the electrolyte also contains additives.

[0089] In some embodiments, the additives include, but are not limited to, at least one of vinylene carbonate (VC), fluoroethylene carbonate (FEC), ethylene sulfate (DTD), trimethylsilane (TMS), lithium difluorophosphate (LiPF2), trimethoxypropane (TMP), and DFE (difluoroethane).

[0090] When the electrolyte additives that can quickly form a thinner and more stable SEI film are selected, not only can the resistance of lithium ions during interfacial transport be reduced, but also the side reactions between the negative electrode and the electrolyte are reduced, thus ensuring cycle stability.

[0091] More preferably, the additive has a mass percentage content of 0.1-30% in the electrolyte.

[0092] In some embodiments, the secondary battery further includes a positive electrode.

[0093] In some embodiments, the positive electrode sheet includes a positive active material layer, which includes a positive electrode material.

[0094] In some embodiments, the porosity of the positive electrode active material layer is 15-50%.

[0095] After adjusting the negative electrode, further optimizing the porosity of the positive electrode active material layer of the secondary battery within the above range can also enable the positive electrode active material layer to have a high liquid retention capacity, reduce the lithium ion transport resistance, and at the same time avoid increasing the side reactions between the electrode and the electrolyte due to excessive wetting, thus ensuring better fast charging performance and cycle stability.

[0096] It should be noted that the porosity of the positive electrode active material layer described in this application can be confirmed by, but is not limited to, the following methods: The positive electrode sheet was cut into circular pieces with a diameter of D = 12 mm. Simultaneously, a thickness gauge was used to measure the thickness of the electrode sheet and the current collector, recording the results as h1 and h2 respectively. This was then calculated using V1 = πR. 2 Calculate the volume V1 of the positive electrode active material layer using (h1-h2), then weigh the electrode and record the mass as m1. Next, immerse the electrode completely in a sealed container of hexadecane for 1 hour (the volume of hexadecane in the sealed container is not critical, but the amount must be sufficient to completely submerge the electrode). Remove the electrode and dry it with filter paper until a constant weight is achieved (generally after 1 hour). Weigh the electrode and record the weight as m2. Calculate the porosity of the positive electrode active material layer using the formula porosity% = (m2-m1 / ρ) / V1 × 100%, where ρ is the density of hexadecane, 0.7734 g / cm³. 3 .

[0097] In some embodiments, the areal density of the positive electrode sheet is 386~500 g / m³. 2 The compacted density is 2.53~2.7 g / cm³. 3 .

[0098] The test methods for the areal density and compaction density of the positive electrode sheet described in this application are the same as those for the negative electrode sheet.

[0099] In some embodiments, the cathode material includes at least one of lithium iron phosphate and lithium nickel cobalt manganese oxide.

[0100] In some embodiments, the cathode material comprises lithium iron phosphate, a% = 35%~45%, and / or b = 2.5~5mΩ.

[0101] When lithium phosphate is selected as the positive electrode material, its overall structural stability is high and the risk of transition metal dissolution is low. By adapting the negative electrode material with a slightly lower proportion of mesoporous pores and adjusting the electrode surface resistance, the electrolyte wetting effect and ion transport rate of the negative electrode sheet can be improved, the transport of lithium ions can be accelerated, and the fast charging performance of the secondary battery can be further improved.

[0102] In some embodiments, the cathode material comprises lithium nickel cobalt manganese oxide, wherein a% = 40%~50%, and / or b = 3~4.4mΩ.

[0103] When lithium nickel cobalt manganese oxide is selected as the positive electrode material, due to the risk of transition metal dissolution, it is necessary to adapt it to a negative electrode material with a slightly higher proportion of mesoporous pores and adjust the electrode surface resistance to reduce the stress impact on the electrode during lithium ion transport, while reducing the activity of interfacial side reactions between the electrolyte and the electrode, thereby further improving the cycle stability of the secondary battery.

[0104] In some embodiments, the lithium iron phosphate includes first lithium iron phosphate particles and second lithium iron phosphate particles, wherein the particle size of the first lithium iron phosphate particles is ≥0.8μm and the particle size of the second lithium iron phosphate particles is ≤0.2μm.

[0105] In some embodiments, the cumulative distribution particle size D of the first lithium iron phosphate particles n50 The thickness is 0.8~5μm.

[0106] In some embodiments, the cumulative distribution particle size D of the second lithium iron phosphate particles n50 The range is 0.01~0.2μm.

[0107] When two different sizes of lithium iron phosphate particles are used as active particles, the smaller lithium iron phosphate particles fill the gaps between the larger particles, significantly improving the lithium insertion / extraction efficiency, shortening the lithium ion transport path, and reducing the degree of side reactions between the electrolyte and lithium iron phosphate particles, resulting in better fast charging performance and cycle stability of the secondary battery.

[0108] In some embodiments, the first lithium iron phosphate particle accounts for 0.2% to 80% of the total lithium iron phosphate particles.

[0109] It should be noted that in the technical solution of this application, the cumulative distribution of the number of first lithium iron phosphate particles and second lithium iron phosphate particles with particle size D n50 Specifically, this can be confirmed through, but is not limited to, the following methods: The secondary battery was discharged at 0.33C to the lower limit of 2.5V for venting treatment, then disassembled. The obtained positive electrode sheet was soaked in dimethyl carbonate (DMC) at 25°C for 2 hours, dried, and then the positive electrode active material layer was scraped off as a sample. The sample was fixed with conductive adhesive, CP argon ion polished, and a conductive film was deposited. It was placed on a sample stage and observed under a scanning electron microscope (SEM). Three areas were selected and photographed at 50Kx magnification. Then, the first and second lithium iron phosphate particles were identified by their particle diameter. The first lithium iron phosphate particles were larger, with a particle size ≥0.8μm, while the second lithium iron phosphate particles were smaller, with a particle size ≤0.2μm. The particle size was measured using measurement software. Then, the first and second lithium iron phosphate particles were located in the area, and the particle size of the first lithium iron phosphate particles was measured. A total of 200 particles were measured, and the particle size distribution of the 50% particle number distribution was calculated, which is the cumulative particle size distribution D of the first lithium iron phosphate particles. n50 The particle size of 200 lithium iron phosphate particles was measured. The particle size distribution of 50% of the particles was calculated, which yields the cumulative particle size distribution D of the lithium iron phosphate particles. n50 .

[0110] In some embodiments, the positive electrode active material layer in the positive electrode sheet includes a positive electrode material, a binder, and a conductive agent, and the mass percentage of the positive electrode material in the positive electrode active material layer is 92-99%.

[0111] In some embodiments, the binder is used to improve the adhesion between cathode material particles and the adhesion between the cathode material and the cathode current collector. Any binder can be used without particular limitation, as long as it has suitable adhesive properties and does not significantly cause adverse chemical changes in the battery. For example, the binder includes fluorinated polyolefin binders, including but not limited to polyvinylidene fluoride (PVDF), PVDF copolymers, or their modified derivatives (e.g., modified with carboxylic acids, acrylic acid, acrylonitrile, etc.).

[0112] Specifically, the adhesive is selected from polytetrafluoroethylene or polyvinylidene fluoride.

[0113] In some embodiments, the mass percentage of the binder in the positive electrode active material layer is 0.5% to 4.0%, such as 0.5%, 1%, 1.2%, 1.5%, 1.8%, 2.0%, 2.2%, 2.5%, 2.7%, 3.0%, 3.2%, 3.5%, 3.8%, 4.0%, or any range formed by any two of the above values.

[0114] In some embodiments, the conductive agent is used to provide conductivity. Any conductive agent can be used without particular limitation, as long as it has suitable electronic conductivity and does not significantly cause adverse chemical changes in the battery. Exemplary examples of conductive agents in the positive electrode active material layer include, but are not limited to, at least one of carbon nanotubes, carbon black, graphite, carbon fibers, activated carbon, mesoporous carbon, and fullerenes, wherein carbon fibers are, for example, carbon nanofibers; and carbon black is, for example, SP (Super P), acetylene black, Ketjen black, etc.

[0115] In some embodiments, the mass percentage of the conductive agent in the positive electrode active material layer is 0.5% to 4%, such as 0.5%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.5%, 3.0%, 4.0%, or any range formed by two of the above values. In some embodiments, the secondary battery also includes a separator.

[0116] In some embodiments, the air permeability of the diaphragm is 50~800 s / 100mL.

[0117] In addition to the electrode end, the present application scheme synchronously regulates the separator, which can effectively ensure the separator's adsorption of electrolyte, improve the rapid transport efficiency of lithium ions, and at the same time avoid the increase of side reactions between electrolyte and the two electrodes, thus achieving higher comprehensive electrochemical performance.

[0118] It should be noted that the air permeability of the separator described in this application can be confirmed by, but is not limited to, the following method: The secondary battery is discharged at 25°C at a rate of 0.33C until the lower voltage limit of 2.5V is reached. The battery is then disassembled and the separator is removed. It is then soaked in DMC for 10 minutes, allowed to air dry, and subsequently tested using an air permeability tester at 25°C under a pressure of 1.21 kPa, allowing 100 mL of air to pass through an area of ​​6.45 cm². 2 The time required for the diaphragm to be formed is expressed in seconds, which gives the air permeability of the diaphragm.

[0119] In some embodiments, the diaphragm includes a basement membrane.

[0120] More preferably, the base film includes at least one of a polypropylene base film and a polyethylene base film.

[0121] In some embodiments, the thickness of the base membrane in the diaphragm accounts for 50-80%.

[0122] The type of base membrane described in this application is not specifically limited, as long as it can achieve the basic support strength required for secondary battery separators, it is acceptable.

[0123] In some embodiments, the diaphragm is further provided with a coating, the coating being disposed on at least one side of the diaphragm, the coating comprising at least one of an organic coating and an inorganic coating, the organic coating containing at least one of aramid and polyvinylidene fluoride, and the inorganic coating comprising at least one of alumina particles, silica particles, titanium dioxide particles, and composite oxide ceramic particles.

[0124] In some embodiments, the thickness of the diaphragm is 12~40 μm.

[0125] The present invention is further illustrated below with specific embodiments, which should not be construed as limiting the scope of protection claimed by the present invention: Example 1 A secondary battery, the preparation method comprising the following steps: (1) Preparation of negative electrode material: Petroleum coke was pulverized and calcined at 800℃ for 3h under nitrogen atmosphere at a heating rate of 5℃ / min, followed by graphitization treatment at 2500℃ for 7h to obtain the particle size D. v50 It is a 12μm negative electrode material; (2) Preparation of negative electrode sheet: In the negative electrode material, the negative electrode material, conductive agent (a mixture of SP and carbon nanotubes, with carbon nanotubes accounting for 60% by mass), thickener sodium carboxymethyl cellulose, and binder styrene-butadiene rubber are dispersed in water at a mass percentage of 95.5%:1.5%:1.5%:1.5%, and D is mixed in. v50 The negative electrode sheet is obtained by adding 0.35% by mass of mesoporous silica to the total material (including negative electrode material, conductive agent, thickener, binder, and mesoporous material) and preparing a slurry by vacuum stirring. The slurry is then coated onto a current collector copper foil, dried, and rolled at 100 MPa to obtain the negative electrode sheet. The areal density of the negative electrode sheet is 200 g / m³. 2 The compacted density is 1.7 g / cm³. 3 ; (3) Preparation of positive electrode sheet: The particle size D v50 Lithium iron phosphate with a thickness of 20 μm was used as the positive electrode material. The positive electrode material, conductive agent acetylene black and binder polyvinylidene fluoride were then dispersed in N-methylpyrrolidone at a mass ratio of 98:1:1. The mixture was vacuum stirred to prepare a slurry, which was then coated onto a current collector aluminum foil. After drying, rolling at 100 MPa and slitting, the positive electrode sheet was obtained. (4) Preparation of electrolyte: EC (ethylene carbonate), EMC (ethyl methyl carbonate) and DEC (diethyl carbonate) are mixed in a volume ratio of 1:1:1 as solvent. Then, based on the total mass of the electrolyte, lithium hexafluorophosphate is added to prepare a lithium hexafluorophosphate concentration of 1 mol / L, and VC with a mass percentage of 4% is added as an additive to finally obtain the electrolyte. (5) The positive electrode, commercially available PP separator and negative electrode are stacked in sequence to form a battery cell. The battery cell is placed in the outer packaging shell, dried and injected with electrolyte. After vacuum sealing, standing, formation and volume adjustment, the lithium-ion secondary battery is obtained.

[0126] Examples 2-22, Comparative Examples 1-4 A positive electrode sheet and the lithium-ion battery prepared therefrom differ from Example 1 only in the preparation process. The parameters and test results of the products during preparation are shown in Tables 1-2, and the test methods for the parameters of each product are as described above.

[0127] In the negative electrode sheets of Examples 10 and 13, the mesoporous material, mesoporous silica, was replaced with D during the preparation of the negative electrode sheets. v50 The mesoporous material is 8 μm, and the volume percentage of pores with a pore size of 5-50 nm in the total pore volume is 65% of the mesoporous alumina; the positive electrode sheet is prepared with a particle size D v50 Lithium nickel cobalt manganese oxide (NCM811) with a thickness of 30 μm was used as the cathode material.

[0128] In the preparation of the negative electrode sheet and the formulation of the slurry, the total mass content of the conductive agent and the negative electrode material in the material is the same as in Example 1 when the conductive agent content is adjusted in each embodiment and comparative example. That is, the increase or decrease in the mass of the conductive agent is made up by the negative electrode material so that the total mass content of the conductive agent and the negative electrode material remains unchanged.

[0129] Table 1 Continued from Table 1 Continued from Table 1 Table 2 Example of effect The secondary batteries obtained in each embodiment and comparative example were tested as follows: (1) Fast charging test: The battery was placed in a 25°C incubator until thermal equilibrium was reached. It was then charged at a constant current rate of 0.33C to the upper limit voltage (3.65V for Examples 1-9 / 11-12 / 14-22 and Comparative Examples 1-4, and 4.25V for Examples 10 and 13). It was then charged at a constant voltage until the current was less than 0.05C, and then discharged at 0.33C to 2.5V. This process was repeated at least three times to obtain the battery's discharge capacity. The capacity C1 of the secondary battery was recorded. The battery was left to stand for 5 minutes. The battery was then charged to 50% SOC at a discharge rate of 0.33C. It was then discharged at a current rate of 1C for 18 seconds. The battery voltage U2 and current I before the discharge stopped were recorded, and the battery voltage U1 after the battery voltage stabilized was recorded. The DC internal resistance R1 was calculated using the formula R1=(U2-U1) / I. This R1 is the DCR of the 1C discharge at 25°C. The smaller the DCR, the better the fast charging performance.

[0130] (2) Loop testing: The secondary battery was charged at 25°C with a constant current of 1C to the upper limit voltage (3.65V for Examples 1~9 / 11~12 / 14~22 and Comparative Examples 1~4, and 4.25V for Examples 10 and 13), and then charged with a constant voltage until the current dropped to 0.05C; left to stand for 20 minutes; discharged at a 1C rate to 2.5V; left to stand for 20 minutes to obtain the initial capacity A0; Perform 1000 cycle tests following the steps above, record the capacity A1 of the last cycle, and calculate the capacity retention rate = A1 / A0 × 100%. The higher the retention rate, the better the cycle performance.

[0131] The test results are shown in Table 3.

[0132] Table 3 As can be seen from Table 3: (1) In the scheme described in this application, the secondary battery synergistically regulates the pore size distribution of the negative electrode material in the negative electrode sheet, especially the volume ratio a of pores with a pore size ≥ 30 nm, and the electrolyte wetting coefficient c of the negative electrode sheet. This can improve the wetting effect of the negative electrode sheet when it comes into contact with the electrolyte, improve the liquid retention capacity of the negative electrode sheet, and reduce the polarization effect. At the same time, it also regulates the sheet resistance b of the negative electrode sheet, which significantly improves the rate of lithium ion deposition in the negative electrode and reduces the transmission resistance inside the electrode sheet. Ultimately, the secondary battery can not only take into account the cycle stability, but also achieve a capacity retention rate of more than 80% after long cycles in each embodiment. It also has good fast charging performance, and the DCR after testing can be controlled within 100 mΩ. In particular, when the synergistic relationship (a×c) / b of the three is further optimized in the range of 1.9~7, the cycle performance and fast charging performance of the secondary battery can reach a higher level.

[0133] (2) When the volume percentage (a%) of pores larger than 30 nm in the negative electrode material changes, it can affect the wetting efficiency of the electrolyte, thereby affecting the transport of lithium ions. However, it can also affect the activity of interfacial side reactions between the electrode and the electrolyte. After synergistic regulation, if it is further optimized to be in the range of 35% to 55%, the balance between the lithium ion transport performance and interfacial stability of the negative electrode can be further improved. On the other hand, when the sheet resistance of the negative electrode is in a small range, although it can increase the deposition rate of lithium ions at the electrode end, it will also increase the probability of lithium dendrite formation, which will affect the stability of the electrode. Therefore, based on the regulation of the negative electrode, the inventors found that further optimizing its size to be preferably in the range of 2.5 to 10 mΩ can further balance the fast charging and cycle performance of the battery. In addition, the wetting coefficient of the electrode is related to the electrolyte wetting effect of the electrode. After synergistic regulation based on the pore parameters of the negative electrode material and the sheet resistance of the electrode, the wetting coefficient c is further optimized to be in the range of 0.12 to 0.3 mm s. -1 / 2 Within this range, secondary batteries can also achieve better electrochemical performance levels.

[0134] (3) In addition, it can be seen from the various embodiments that when mesoporous oxide is introduced into the negative electrode material, the liquid retention capacity of the negative electrode sheet for electrolyte can be effectively improved, the wetting channel is less blocked, and the lithium ion transport resistance is reduced. In particular, the surface resistance of the negative electrode sheet and the content of mesoporous oxide in the electrode sheet are synergistically matched so that the b / d ratio is in the range of 250~5000, which can effectively improve the liquid retention capacity of the negative electrode sheet, reduce the lithium ion transport resistance inside the electrode sheet, reduce the polarization effect, and at the same time, it will not form lithium dendrites due to the lithium ion deposition rate being too fast, or increase the side reaction between the negative electrode material and the electrolyte due to excessive wetting of the electrolyte, and finally achieve better battery fast charging performance and cycle stability.

Claims

1. A secondary battery, characterized in that, It includes a negative electrode sheet and an electrolyte, wherein the negative electrode sheet includes a negative electrode active material layer, and the negative electrode active material layer includes a negative electrode material; The secondary battery satisfies: (a×c) / b=0.12~53.6; The percentage a% represents the volume percentage of pores with a diameter ≥ 30 nm in the total pore volume of the negative electrode material; a% = 20%~60%; The b mΩ is the surface resistance of the negative electrode plate; b = 0.5~20mΩ; The c mm.s -1 / 2 The electrolyte wetting coefficient of the negative electrode sheet is c = 0.1~0.5 mm.s -1 / 2 ; The secondary battery satisfies: x% = 5%~30%, where x% is the volume percentage of pores with a pore size ≤ 10nm in the negative electrode material in the total pore volume, and / or the secondary battery satisfies: y% = 5%~45%, where y% is the volume percentage of pores with a pore size ≥ 50nm in the negative electrode material in the total pore volume.

2. The secondary battery as described in claim 1, characterized in that, The secondary battery satisfies: (a×c) / b=0.5~5.

5.

3. The secondary battery as described in claim 1, characterized in that, The a% value is 35%~55%, and / or the b value is 2.5~10 mΩ, and / or the c value is 0.12~0.3 mm·s. -1 / 2 .

4. The secondary battery as described in claim 1, characterized in that, The negative electrode material includes mesoporous materials.

5. The secondary battery as described in claim 4, characterized in that, The mesoporous material includes at least one of mesoporous oxides, mesoporous nitrides, mesoporous carbides, and mesoporous organic framework materials.

6. The secondary battery as described in claim 5, characterized in that, The negative electrode material includes a mesoporous oxide, which is an oxide of element X. The mass percentage of element X in the negative electrode active material layer is 0.06-2%, and element X includes at least one of Si, Al, W, Zn, Cu, V, and Ti.

7. The secondary battery as described in claim 6, characterized in that, The secondary battery satisfies: b / d = 250~5000, where d is the mass percentage of element X in the negative electrode active material layer.

8. The secondary battery as described in claim 1, characterized in that, The tortuosity of the negative electrode sheet is 3~15.

9. The secondary battery as described in claim 1, characterized in that, The negative electrode material includes at least one of graphite and silicon-based materials.

10. The secondary battery as described in claim 1, characterized in that, The particle size D of the negative electrode material v50 The value is 3~20μm.

11. The secondary battery as described in claim 1, characterized in that, The viscosity of the electrolyte at 25°C is 1~10 mPa·s.

12. The secondary battery as described in claim 11, characterized in that, The electrolyte comprises a solvent and a lithium salt. The solvent comprises at least one of carbonate solvents, carboxylic acid ester solvents, ether solvents, sulfone solvents, nitrile solvents, and phosphate ester solvents, and / or the lithium salt comprises at least one of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium dioxalate borate, lithium difluorooxalate borate, lithium trifluoromethanesulfonate, lithium difluorosulfonylimide, lithium difluoromethanesulfonylimide, lithium ditrifluoromethanesulfonylimide, lithium difluorodioxalate phosphate, lithium tetrafluorooxalate phosphate, and lithium hexafluoroarsenate.

13. The secondary battery as described in claim 1, characterized in that, The electrolyte also contains additives, including at least one of vinylene carbonate, fluoroethylene carbonate, ethylene sulfate, trimethylsilane, lithium difluorophosphate, trimethoxypropane, and difluoroethane.

14. The secondary battery as described in claim 13, characterized in that, The additive has a mass percentage content of 0.1-30% in the electrolyte.

15. The secondary battery as described in claim 1, characterized in that, The secondary battery also includes a positive electrode sheet, which includes a positive active material layer, and the positive active material layer includes a positive electrode material.

16. The secondary battery as described in claim 15, characterized in that, The porosity of the positive electrode active material layer is 15-50%.

17. The secondary battery as described in claim 16, characterized in that, The cathode material includes at least one of lithium iron phosphate and lithium nickel cobalt manganese oxide.

18. The secondary battery of claim 17, wherein the positive electrode material comprises lithium iron phosphate, characterized in that, a% = 35%~45%, and / or b = 2.5~5mΩ.

19. The secondary battery as described in claim 18, characterized in that, The positive electrode material includes lithium nickel cobalt manganese oxide, wherein a% = 40%~50%, and / or b = 3~4.4mΩ.

20. The secondary battery as described in claim 18, characterized in that, The lithium iron phosphate comprises first lithium iron phosphate particles and second lithium iron phosphate particles, wherein the particle size of the first lithium iron phosphate particles is ≥0.8μm and the particle size of the second lithium iron phosphate particles is ≤0.2μm.

21. The secondary battery as described in claim 20, characterized in that, The cumulative distribution of the first lithium iron phosphate particles by particle size D n50 The particle size D of the second lithium iron phosphate particles is 0.8~5 μm, and / or the cumulative distribution of the number of particles is... n50 The range is 0.01~0.2μm.

22. The secondary battery as described in claim 20, characterized in that, The first lithium iron phosphate particle accounts for 0.2% to 80% of the total lithium iron phosphate particles.

23. The secondary battery as described in claim 1, characterized in that, The secondary battery also includes a separator, the air permeability of which is 50~800 s / 100mL.

Citation Information

Patent Citations

  • Battery

    CN121215681A

  • Secondary battery

    CN121506922A